My eight book - Moncure, Jane Belk (Elgin, Illinois : The Child's World, 1985)
Little Eight introduces the concept of "eight" by interacting with eight of a number of things, some of which are grouped to further expose the reader to subtracting and dividing.
Keywords: Eight (the number) -- Juvenile literature; Number concept; Counting